Analisis Penyaluran Qard Hasan Menurut Tinjauan Hukum Islam pada Bank Wakaf Mikro Alpen Barokah Mandiri di Pragaan Sumenep Madura - Ningsih, Astri (Ijtihad, 2023)
**English**The presence of BWM Alpen Barokah Mandiri with the channeling of funds in the form of financing using the qard al-hasancontract, is expected to be able to solve the problems that occur in capitalization in the business sector. So that the standard of living of the community is increasing. The existence of this capital grant is expected to be able to encourage the enthusiasm of business actors to improve their businesses. This research aims to analyze of channeling qard al-hasanat BWM Alpen Barokah Mandiri whether or not it is in accordance with Fatwa DSN MUI No 19/DSN-MUI/IV/2001. The type of research used is qualitative descriptive with interview, observation and documentation methods. The results of this study are that for distributing qard al-hasanat the Alps Barokah Mandiri Micro Waqf Bank is in accordance with the DSN-MUI Fatwa No 19/DSN-MUI/IV/2011 and the SOP for distributing qard al-hasanBWM Alps Barokah Independent because it is carried out with the identification stage, the socialization stage, the due diligence stage, the PWK (Compulsory Group Training) and HALMI (Weekly Halaqoh) stages. Although in the distribution of qard al-hasanat the Alps Barokah Mandiri Micro Waqf Bank does not have the Opinion of the Sharia Supervisory Board. This indicates that the DPS work rules are not optimal in implementing good corporate governance. **Indonesia**Kehadiran BWM Alpen Barokah Mandiri dengan penyaluran dana dalam bentuk pembiayaan menggunakan akad qard al-hasan, diharapkan mampu menyelesaikan masalah yang terjadi dalam permodalan di sektor usaha. Sehingga taraf hidup masyarakat semakin meningkat. Adanya pemberian modal ini diharapkan mampu mendorong semangat para pelaku usaha untuk mengembakan usaha yang dimiliki. Penelitian ini bertujuan untuk menganalisis mekanisme penyaluran  qard al-hasan pada BWM Alpen Barokah Mandiri apakah sudah sesuai atau tidak dengan Fatwa DSN MUI No 19/DSN-MUI/IV/2001. Jenis penelitian yang digunakan adalah deskriptif kualitatif dengan metode wawancara, observasi dan dokumentasi. Hasil penelitian ini yaitu penyaluran qard al-hasan di Bank Wakaf Mikro Alpen Barokah Mandiri sudah sesuai dengan Fatwa DSN-MUI No 19/DSN-MUI/IV/2011 dan SOP penyaluran qard al-hasan BWM Alpen Barokah Mandiri karena dilakukan dengan tahap identifikasi, tahap sosialisasi, tahap uji kelayakan, tahap PWK (Pelatihan Wajib Kelompok) dan HALMI (Halaqoh Mingguan). Meskipun dalam penyaluran qard al-hasan di Bank Wakaf Mikro Alpen Barokah Mandiri tidak memiliki Opini Dewan Pengawas Syariah. Hal ini menandakan bahwa tidak optimalnya tata tertib kerja DPS dalam menerapkan tata kelola perusahaan yang baik.